2020
DOI: 10.1128/jcm.00941-20
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of the Abbott Architect SARS-CoV-2 IgG Assay and Seroprevalence in Boise, Idaho

Abstract: 22Coronavirus disease-19 (COVID19), the novel respiratory illness caused by severe acute 23 respiratory syndrome coronavirus 2 (SARS-CoV-2), is associated with severe morbidity and 24 mortality. The rollout of diagnostic testing in the United States was slow, leading to numerous 25 cases that were not tested for SARS-CoV-2 in February and March 2020, necessitating the use 26 of serological testing to determine past infections. Here, we evaluated the Abbott SARS-CoV-2 27IgG test for detection of anti-SARS-CoV-2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
518
10
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 549 publications
(571 citation statements)
references
References 10 publications
37
518
10
6
Order By: Relevance
“…At this point, serology may be the only method to track down past/cured infected patients. Here, we con rm the observations by Bryan et al, who reported no IgG detection in samples taken from patients during periods before the COVID pandemic using Architect Abbott´s SARS-CoV-2 IgG [16]. Furthermore, we show the same lack of cross-reactivity in the PanbioTM COVID-19 IgG/IgM rapid test device.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…At this point, serology may be the only method to track down past/cured infected patients. Here, we con rm the observations by Bryan et al, who reported no IgG detection in samples taken from patients during periods before the COVID pandemic using Architect Abbott´s SARS-CoV-2 IgG [16]. Furthermore, we show the same lack of cross-reactivity in the PanbioTM COVID-19 IgG/IgM rapid test device.…”
Section: Discussionsupporting
confidence: 91%
“…Bryan et al report 100% sensitivity in cases for which samples were taken ≥17 days from the onset of the disease. The results communicated by these authors are signi cantly higher than the ones reported in our study [16]. Here, we tested patients who attended the emergency department with acute and active clinical presentations (Cohort 1).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…No Paediatric patients (<18 years) developed COVID-19 disease or screened positive for the disease and patients with CKD not on renal replacement therapy, renal transplant recipients and patients with acute kidney injury requiring dialysis were excluded. (11). These and other diagnostics tests had regular and routine quality control as expected within an accredited pathology network.…”
Section: Study Design and Participantsmentioning
confidence: 99%